Redeployment in language contact: the case of phonological emphasis - Flynn, Darin (Frontiers in Language Sciences, 2024)
This article applies the notion of redeployment in second language acquisition to contact-induced diachronic changes. Of special interest are cases where a marked phonological contrast has spread across neighboring languages. Such cases suggest that listeners can re-weight and re-map phonetic cues onto novel phonological structures. On the redeployment view, cues can indeed be re-weighted, but phonological structures which underlie a new contrast are not expected to be fully novel; rather, they must be assembled from preexisting phonological structures. Emphatics are an instructive case. These are (mostly) coronal consonants articulated with tongue-root retraction. Phonological emphasis is rare among the world's languages but it is famously endogenous in Arabic and in Interior Salish and it has spread from these to not a few neighboring languages. The present study describes and analyzes the genesis of phonological emphasis and its exogenous spread to a dozen mostly unrelated languages—from Arabic to Iranian and Caucasian languages, among others, and from Interior Salish to Athabaskan and Wakashan languages. This research shows that most languages acquire emphatics by redeploying the phonological feature [RTR] (retracted tongue root) from preexisting uvulars. On the other hand, some languages acquire imitations of emphatics by redeploying the consonantal use of [low] from preexisting pharyngeals. Phonological emphasis is apparently not borrowed by neighboring languages where consonants lack a phonological feature fit for redeployment. The overall impression is that a language in contact with emphatics may newly adopt these sounds as [RTR] or [low] only if the relevant feature is already in use in its consonant system. This pattern of adoption in language contact supports the redeployment construct in second language acquisition theory.